Max Weber's 'Objectivity' Reconsidered - McFalls, Laurence H. (Book collections on Project MUSE., 2007)
"The German sociologist Max Weber (1864-1920) is without question one of the founders of modern social science. In his methodological writings, notably his essay "The 'Objectivity' of Knowledge in Science and Policy" (1904), Weber sought reflexively to establish a trans-culturally valid basis for the historical and cultural sciences. Over the past century, however, his work has given rise to divergent interpretations and practical applications within different disciplinary and cultural contexts. In Max Weber's 'Objectivity' Reconsidered, Laurence H. McFalls and a distinguished group of contributors explore the fragmented reception of Weber's work and the legacies of his methodological writings for contemporary social science, offering their appraisals of Weber's successes and failures in laying the groundwork for an 'objective' social science. They develop a 'Weberian' theory of his reception and evaluate the possibility of an 'objectively' valid Weberian social science today. This essential volume not only contributes to the resurgence of interest in Weber's oeuvre but goes beyond the exegetic and polemical debates of the burgeoning 'Weberological' literature in offering a coherent theoretical explanation for the proliferation of interpretations that Weber's writings continue to elicit."--